Advanced Join Strategies for Large-Scale Distributed Computation - Bruno, Nicolas; Kwon, YongChul; Wu, Ming (Proc. VLDB Endow., 2014)
Companies providing cloud-scale data services have increasing needs to store and analyze massive data sets (e.g., search logs, click streams, and web graph data). For cost and performance reasons, processing is typically done on large clusters of thousands of commodity machines by using high level scripting languages. In the recent past, there has been significant progress in adapting well-known techniques from traditional relational DBMSs to this new scenario. However, important challenges remain open. In this paper we study the very common join operation, discuss some unique challenges in the large-scale distributed scenario, and explain how to efficiently and robustly process joins in a distributed way. Specifically, we introduce novel execution strategies that leverage opportunities not available in centralized scenarios, and others that robustly handle data skew. We report experimental validations of our approaches on Scope production clusters, which power the Applications and Services Group at Microsoft.